Studi Validitas Hadis-Hadis Dalam Ayqâz An-Niyâm Karya Syeikh Abdul Karim Amrullah (W.1945) - Sukma Dahlia (Al-Mu'tabar, 2024)
This study examines the validity of the Hadiths contained in the book of Ayqâz an-Niyâm Fima Ibtada’a min Amril Qiyâm, in which there is the thought of Abdul Karim Amrullah about the implementing of standing on readings of the Maulid Prophet. He wrote in his work as a means of praise and tablig in purifying the practices of the values of the teachings of Islam that have been contaminated with bid’ah, taklid, and khurafat, for it to be consistent with Minangkabau customary thinking. This research uses a qualitative approach to describe the findings in the book in a descriptive way. To test the validity of the Hadiths contained in the Book of Ayqâz an-Niyâm, the writer uses the method of Takhrij by searching the mother books of Hadith and the book of takhrij hadith. Technically, in some of Abdul Karim's hadiths, he did not write the whole hadith, but after Takhrij, all of the matan hadiths listed in the book were written with complete and qualified Shahih. Nevertheless, the hearts of the hadith used by the elders are felt to be inappropriate to the target and there is a hearing of the Hadith in accordance with the needs of the opinion. This is the basis for the use of Hadith as Hujjah by Abdul Karim Amrullah as a form of opposition to the thought of the Elders in Minangkabau.